Alternative Computer Cursor Shifts for Large Amplitude Eyesight Jumps - Laurutis, V.; Niauronis, S.; Zemblys, R. (Elektronika ir Elektrotechnika, 2010)
The purpose of this research was to investigate alternative control of the computer cursor based on the application of large amplitude gaze shifts of the user. Instead of manual control, proposed algorithm redefines cursor to the new place on the computer screen, where eyesight of the user is directed. Amplitude and velocity of the saccadic eye movement of the user are used as input parameters for cursor redirection. Two options of the redirection of computer cursor: passive and active were investigated. During passive option, used for reading only, computer cursor is ready to appear in the new place onto computer screen but is not activated (not shows up) with the purpose not to disturb the vision. During passive mode, supplement manual input signal is used to activate computer cursor in the new position onto the screen. During active mode, computer cursor is always activated in the position, where eyesight of the user is directed. Experimental investigation of the new alternative method of cursor control was performed using eye tracker EyeGaze System produced by LC Technologies Ltd. and program, developed in our laboratory. The parameters of the program were optimized in the most comfortable way for the user. Effectiveness of the alternative cursor control during real visuo-motor tasks was investigated.